Low-temperature control of nanoscale molecular dynamics
A novel in situ probe of the nanoscale molecular dynamics of organic-molecule and fullerene-tube nanostructures is proposed. General and consistent results for the nonlinear-current coupling to the nanostructure excitations are presented to document a frequency-selective electrostatic control of this current stimulation and optimal operation as a local source of current-induced molecular excitations Wi. The control is possible for temperatures T